PENEGAKAN HUKUM DALAM SISTEM PERADILAN PIDANA BERAZASKAN PANCASILA - Noenik Soekorini (Lex Journal: Kajian Hukum & Keadilan, 2017)
The enforcement of criminal law starts from the legislative body that is the legislative body that makes the law and determines the norms in the form of orders and prohibitions. The legislation made by this legislative body can reflect the existence of the values of justice desired by the principle of Pancasila that is civilized or dignified justice. Criminal law enforcement is also done by the judiciary. That is the application of criminal law in the form of law by law enforcement officers either ranging from the police level to the courts. They are concrete justice enforcers. And the last is related to facilities and infrastructure that support the policy for criminal law enforcement. The process of criminal law enforcement can be effective if there is a harmony relationship starting from the investigation / investigation process at the police, prosecutor / prosecutor level until the court process and ending with the judges verdict. The legislator in this case is the legislative must be able to make regulations that can be implemented in the field. Law enforcers in carrying out their duties must be able to work professionally so as to create a sense of justice for the parties both for the perpetrator and for the victim of the crime.